Deterministic mechanisms define the long-term anaerobic digestion microbiome and its functionality regardless of the initial microbial community. (15th September 2018) - Peces, M.; Astals, S.; Jensen, P.D.; Clarke, W.P.
Abstract: The impact of the starting inoculum on long-term anaerobic digestion performance, process functionality and microbial community composition remains unclear. To understand the impact of starting inoculum, active microbial communities from four different full-scale anaerobic digesters were each used to inoculate four continuous lab-scale anaerobic digesters, which were operated identically for 295 days. Digesters were operated at 15 days solid retention time, an organic loading rate of 1 g COD Lr −1 d −1 (75:25 - cellulose:casein) and 37 °C. Results showed that long-term process performance, metabolic rates (hydrolytic, acetogenic, and methanogenic) and microbial community are independent of the inoculum source. Digesters process performance converged after 80 days, while metabolic rates and microbial communities converged after 120–145 days. The convergence of the different microbial communities towards a core-community proves that the deterministic factors (process operational conditions) were a stronger driver than the initial microbial community composition. Indeed, the core-community represented 72% of the relative abundance among the four digesters. Moreover, a number of positive correlations were observed between higher metabolic rates and the relative abundance of specific microbial groups. These correlations showed that both substrate consumers and suppliers trigger higher metabolic rates, expanding the knowledge of the nexus between microorganisms and functionality. Overall, these results support that deterministic factors control microbial communities in bioreactors independently of the inoculum source. Hence, it seems plausible that a desired microbial composition and functionality can be achieved by tuning process operational conditions. Highlights: Deterministic factors define long-term performance of 4 separately seeded digesters. Process performance converged after 80 days, microbiome converged after 145 days. Digesters shared 52% of OTUs, representing 72% of the relative abundance. Activity rates correlated with both substrate consumers and producers. Activity and microbiome correlation suggested the functionality of some taxa.